In vitro antifungal activity of Cassia fistula L. against selected pathogenic water molds - Manassanan Borisutpeth; Pithai Kanbutra; Sompoth Weerakhun; Shinpei Wada; Kishio Hatai (International Journal of Phytomedicine, 2014)
Water mold infections in both cultured and wild aquatic animals, caused by members of the genera Saprolegnia, Achlya, and Aphanomyces, have widely occurred worldwide. Outbreaks in aquatic creatures, especially in aquacultural facilities and fish hatcheries are common problem. Cassia fistula L. has been used as medicinal plant for broad purposes including for fungal infectious diseases remedy, but efficacy against water molds is still not apparently known. The present study was aimed to investigate in vitro antifungal activity of C. fistula stem-bark alcoholic extracts against the selected pathogenic water molds isolated from fish. The results showed that the C. fistula extract was capable to kill hyphae and zoospores of Saprolegnia paracitica NJM 8604 and S. diclina NJM 0005 at levels ranging from 1,000-4,000 microg/mL evidently within 24 h-exposure, while, a level of 500 microg/mL was sufficient to kill the both stages of Aphanomyces invadans NJM 9701. In addition, the antifungal activity of C. fistula absolute alcoholic extract comparing to 50% aqueous alcoholic extract were seemingly not different. Conclusively, the C. fistula stem-bark extracts, both absolute and 50% aqueous alcoholic extractions, were effectively able to inhibit growth and kill the 3 strains of pathogenic water molds by affect throughout the 2 important, zoospore and hyphal, stages.